Knowledge Management in Health Care Education - Judita Peterlin; Vlado Dimovski; Simon Colnar; Sandra Penger; Barbara Grah (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
Knowledge management is a vital source of sustainable competitive advantage in all social areas, including health care. In this paper, we present insight into previous knowledge of students of health care related to the management domain and their expectations regarding what they aim to gain at the course. We collected 57 valid data entries, 42 females and 15 males, and analyzed it by using the content analysis. The average age of our respondents was 21 years. Results are presented, and key identified themes offer several educational implications. Students wish to learn organizational techniques, team management tools, and leadership development tools, mainly.
Keywords: I21; 330; Knowledge; management; health care; students